PEMINDAHAN ARSIP DI CENTRAL FILE BIDANG TRANSMIGRASI KE RECORDS CENTER DINAS TENAGA KERJA DAN TRANSMIGRASI DAERAH ISTIMEWA YOGYAKARTA - , ENI WIDIASTUTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The thesis desribes the remoral prosedures archives from central file to records center. are still in a state at not reqularly so must make arragement before being transferred to the record center. The following removal procedure by sorting the records and non records, archive filling made by the problems. Preparation of a list of arhives giving the serial number, chasing, enter archive in the box and accompanied by the implementation of transfer of news and events. Method of data collection is done throught three stages. The first observation to observation and prastice participation dirctly records management practive in order to depreciation. The second method is a direct interview with the otticer in the archives. The third book study using both methods with appropriate references to the themes and relevan. secondary data in the form of a decree, JRA is used to make an assessment of the active to the inactive file and the latter with the use, The Organizational Structure is used to know origin of the archive. The main conclusion of this final task is the implementation of the archives of the department shrink Labour and Transmigration is still in the context of irregular transfer of the archives. Before the transplant, there should be setup prior to the archive records to be transferred already in place. Before performing the displacement, there must be structuring in advance so that the archive file to be transferred is already in a disordered state.